Potassium Intake and Blood Pressure: A Dose-Response Meta-Analysis of Randomized Controlled Trials - Filippini, T (2020)
Background. Epidemiologic studies, including trials, suggest an association between potassium intake and blood pressure (BP). However, the strength and shape of this relationship is uncertain. Methods and Results. We performed a meta‐analysis to explore the dose‐response relationship between potassium supplementation and BP in randomized‐controlled trials with a duration ≥4 weeks using the recently developed 1‐stage cubic spline regression model. This model allows use of trials with at least 2 exposure categories. We identified 32 eligible trials. Most were conducted in adults with hypertension using a crossover design and potassium supplementation doses that ranged from 30 to 140 mmol/d. We observed a U‐shaped relationship between 24‐hour active and control arm differences in potassium excretion and BP levels, with weakening of the BP reduction effect above differences of 30 mmol/d and a BP increase above differences ≈80 mmol/d. Achieved potassium excretion analysis also identified a U‐shaped relationship. The BP‐lowering effects of potassium supplementation were stronger in participants with hypertension and at higher levels of sodium intake. The BP increase with high potassium excretion was noted in participants with antihypertensive drug‐treated hypertension but not in their untreated counterparts. Conclusions. We identified a nonlinear relationship between potassium intake and both systolic and diastolic BP, although estimates for BP effects of high potassium intakes should be interpreted with caution because of limited availability of trials. Our findings indicate an adequate intake of potassium is desirable to achieve a lower BP level but suggest excessive potassium supplementation should be avoided, particularly in specific subgroups.